OECD employment outlook 2014 (Paris, 2014)
"The OECD Employment Outlook 2014 marks the 20th Anniversary of the OECD Jobs Strategy and includes chapters on recent labour market developments with a special section on earnings/wages, job quality, youth employment, unemployment and unemployment rates, and forms of employment and employment protection. As in previous editions, the 2014 OECD Employment Outlook monitors recent labour market developments in OECD countries and Key Partner economies and identifies appropriate policy action to foster more and better jobs."